A C1-symmetric N-heterocyclic carbene catalysed oxidative spiroannulation of isatin-derived enals: highly enantioselective synthesis of spirooxindole δ-lactones. Issue 28 (24th April 2018) - Lin, Jun-Bing; Cheng, Xi-Na; Tian, Xiao-Dong; Xu, Guo-Qiang; Luo, Yong-Chun; Xu, Peng-Fei
Abstract : A NHC-catalysed spiroannulation of isatin-derived enals and 1, 3-dicarbonyl compounds has been developed, enabling enantioselective synthesis of synthetically important spirooxindole δ-lactones. Abstract : A C1 -symmetric N -heterocyclic carbene (NHC)-catalysed activation of isatin-derived enals under oxidative conditions was achieved. The in situ generated α, β-unsaturated acyl azolium species was efficiently trapped by 1, 3-dicarbonyl compounds via a Michael addition/spiroannualtion cascade, delivering a series of synthetically important spirooxindole δ-lactones with up to 96% enantioselectivity.